1963
DOI: 10.1152/jappl.1963.18.2.264
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary capillary blood volume in dog: effects of 5-hydroxytryptamine

Abstract: We studied changes in pulmonary capillary blood volume (Vc) in anesthetized dogs to determine whether 5-HT (5-hydroxytryptamine) constricts pulmonary venules. The preparation was sufficiently stable to allow reproducible measurement of pulmonary diffusing capacity (Dl). A fixed volume of CO gas mixture was introduced into the lungs by positive pressure, and an alveolar sample was obtained after 10 sec. By measuring Dl at different levels of Pao2, a value proportional to Vc was obtained. We cannot give absolute… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

1965
1965
1998
1998

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(7 citation statements)
references
References 0 publications
1
6
0
Order By: Relevance
“…Several studies have shown venous constriction (14,15), whereas others have found predominant arterial constriction (16,17). Our findings help explain many of the seemingly conflicting results in the literature.…”
Section: Methodssupporting
confidence: 60%
“…Several studies have shown venous constriction (14,15), whereas others have found predominant arterial constriction (16,17). Our findings help explain many of the seemingly conflicting results in the literature.…”
Section: Methodssupporting
confidence: 60%
“…In the dose employed by Shepherd, Donald, Linder, and Swan (2) and by us, no change in total pulmonary blood volume was demonstrated, whereas an increase in serotonin dose of some 15-fold, as used by McGaff and Milnor (29), produced a significant fall in pulmonary blood volume. Pulmonary capillary blood volume measured during a comparable dose given to our dogs rose 29%o with a wide degree of scatter (30).…”
Section: Resultsmentioning
confidence: 72%
“…Excretion of CO that occurs via the lungs is principally a function of alveolar ventilation (VA), the diffusing capacity of the lung (Dco), and the mean oxygen tension in pulmonary capillary blood (12). Both Dco (31) and VA are smaller in dog than in man, and it is therefore likely that the higher [COHb] /Vco found in dogs is explainable on this basis.…”
Section: Introductionmentioning
confidence: 99%